Clinical utility of heparin‐binding protein as an acute‐phase inflammatory marker in interstitial lung disease. Issue 4 (14th February 2022) - Xue, Mingshan; Zhang, Teng; Lin, Runpei; Zeng, Yifeng; Cheng, Zhangkai Jason; Li, Ning; Zheng, Peiyan; Huang, Huimin; Zhang, Xiaohua Douglas; Wang, Hongman; Sun, Baoqing
Abstract: The role of heparin‐binding protein (HBP) as an acute inflammatory marker in acute exacerbations of interstitial lung disease (AE‐ILD) and some stable ILD patients is not well‐established. The significance of increasing HBP during an AE‐ILD is examined and the first attempt to incorporate HBP into the ILD evaluation system is made. Then, the benefit of HBP in AE‐ILD was investigated. ILD patients ( n  = 108) were divided into subgroups based on the phase and severity of the disease. Linear trends of HBP across subgroups were observed, and correlations with common inflammatory markers were examined. Further, the HBP detection was adopted between serum and bronchoalveolar lavage fluid (BALF). Imaging and pathology changes were evaluated using various scoring criteria and compared to HBP. The relationship between HBP with ventilation, fibrosis progression, and changes in arterial oxygen levels and inflammatory markers were investigated to understand the mechanistic pathways. HBP was significantly higher in patients with AE‐ILD at the early stage, compared to patients with ILD at the stable phase and its increase was both found in the serum and BALF. With the remission of the disease, there was a linear trend of progressive decline. HBP identified ILD patients who had co‐infections. HBP levels increased earlier than CRP, PCT, and SAA. HBP was associated with pulmonary levels of ventilation and lesions by radiology examination, and its levels were significantly worse in AE‐ILD patients. However, HBP did not show a correlation to the pathology quantitative evaluation. In conclusion, HBP could potentially evaluate the progression and prognosis of AE‐ILD. Because ILD patients are susceptible to infection, and since HBP can identify co‐infection, this marker would be of great clinical importance. HBP is possibly predictive of acute exacerbation. Graphical Abstract: HBP, which has the functions of inflammatory and fibrotic induction, as well as the advantage of pre‐sythesis for faster release, is an important predictor of the risk of acute exacerbation of ILD.